Ethical-affective (in)dispositions in mobilizing “lugar de fala” (place of speech) concept in computarized enunciative spaces - Campos, Jefferson Gustavo dos Santos (2023)
Under Foucauldian theorization and Discourse Analysis bias, the concept “lugar de fala” (place of speech) is thematized as a strategy for establishing consensus on who is or is not able to speak within a given discursive order. It is based on the hypothesis that the effects of computerized enunciative spaces on the material conditions of these sayings are neglected, as well as the complex relationships among power and resistance in the constitution of the subjectivities involved in the theoretical-militant debate are desregarded. Thus, the existence of ethical-affective (in)dispositions implicated in the theoretical and practical scope of the issue is outlined. Such (in)dispositions corroborate meanings of (in)equality in dispute in contemporary capitalist Society.